Emission characteristics and inventory of volatile organic compounds from the Chinese cement industry based on field measurements. (1st January 2023) - Bai, Xiaoxuan; Liu, Wei; Wu, Bobo; Liu, Shuhan; Liu, Xiangyang; Hao, Yan; Liang, Weizhao; Lin, Shumin; Luo, Lining; Zhao, Shuang; Zhu, Chuanyong; Hao, Jiming; et al.
Abstract: Volatile organic compounds (VOCs) are major precursors of ozone (O3 ) and secondary organic aerosols (SOA), which degrade air quality and pose a serious risk to human health and ecological systems. Previous studies on the emission characteristics of VOCs have predominantly focused on petrochemical and solvent-using sources, while localized studies on the cement industry are scarce in China. Field measurements for four cement plants were carried out in this study to investigate the emission levels, source profiles, and secondary pollutant generation potential of 98 VOCs species emitted from rotary and shaft kilns in China. Furthermore, a species-differentiated VOCs emission inventory was compiled for the Chinese cement industry in 2019. The results demonstrated that the mass concentration of VOCs emitted from shaft kiln was more than 20-fold higher than that emitted from rotary kilns, and the alkanes was the dominant species (56%) in shaft kilns, while oxygenated VOCs (OVOCs) and halocarbons were the main species in rotary kilns. Moreover, alkenes & alkyne were the dominant contributors to ozone formation potential (OFP) in shaft kilns, whereas alkenes & alkyne and OVOCs were comparable and prominent contributors in rotary kilns. In contrast, secondary organic aerosol potential (SOAP) for the two types of kilns was dominated by aromatics. In 2019, approximately 18.18 kt VOCs were emitted from cement production and were found to be largely concentrated in the southeast and central provinces of China. Considering the influence on environmental conditions, high OFP-contributing species in cement kilns are suggested to be a priority in the pollution mitigation of O3 . This study provides a new, comprehensive, and reasonable cognition of the current VOCs emissions from both rotary and shaft kilns in China, which will aid in a better understanding of VOCs emission characteristics and guide future policy-making. Graphical abstract: Image 1 Highlights: Oxygenated VOCs (32%) and halocarbons (28%) are the main species in rotary kilns. Alkanes is the dominant species (56%) in shaft kilns. VOCs emission factors of the shaft and rotary kilns are 0.32 and 0.01 g/kg-clinker. About 18.18 kt VOCs emissions were emitted from cement kilns in China in 2019. Emissions are highly concentrated in the central and southeast provinces of China.